Environmental suitability and yield performance of pulse varieties in Northeastern region of Bangladesh: Pulse Performance in Northeastern Bangladesh - Jahan, Samia; Mridha, Raj; Hoque, Mozammel; Islam, Md Nazrul (Journal of the Sylhet Agricultural University, 2026)
Pulses (Pisum sativum L.) are important grain legume crops that contribute significantly to Bangladesh's nutritional security as inexpensive, high-protein food sources. This research assessed the agronomic performance and environmental adaptability of four pea varieties (Pea Nator Local, Pea Jikorgacha Local, BARI Khesari-2, and BARI Motorshuti-3) at the experimental field of Sylhet Agricultural University during the 2019-2020 Rabi season. The experiment employed a Randomized Complete Block Design (RCBD) with four replications. The results showed significant variation among varieties for plant population, leaves plant⁻¹, branches plant⁻¹, plant height, fresh weight of plant, pods plant⁻¹, pod length, seeds pod⁻¹, 100 seeds weight, and seed yield. The results revealed that the highest seed yield was obtained from Natore local (1572.37 kg ha⁻¹) and it was similar to Jhikorgacha local (1440 kg ha⁻¹). The lowest seed yield was obtained from BARI motorshuti-3 (961.87 kg ha⁻¹). Environmental suitability analysis showed that Pea Nator local had perfect adaptation with 5.5% yield loss while BARI motorshuti-3 suffered 38.8% yield loss due to environmental stress. Above all Pea Nator local and Jikorgacha local may be suggested to farmers to cultivate in Sylhet. J. Sylhet Agril. Univ. 12(2): 77-86, 2025